Costs and consequences: Hepatitis C seroprevalence in the military and its impact on potential screening strategies. Issue 2 (9th December 2015) - Brett‐Major, David M.; Frick, Kevin D.; Malia, Jennifer A.; Hakre, Shilpa; Okulicz, Jason F.; Beckett, Charmagne G.; Jagodinski, Linda L.; Forgione, Michael A.; Gould, Philip L.; Harrison, Stephen A.; Murray, Clinton K.; Rentas, Francisco J.; et al.
Abstract : Knowledge of the contemporary epidemiology of hepatitis C viral (HCV) infection among military personnel can inform potential Department of Defense screening policy. HCV infection status at the time of accession and following deployment was determined by evaluating reposed serum from 10, 000 service members recently deployed to combat operations in Iraq and Afghanistan in the period 2007‐2010. A cost model was developed from the perspective of the Department of Defense for a military applicant screening program. Return on investment was based on comparison between screening program costs and potential treatment costs avoided. The prevalence of HCV antibody‐positive and chronic HCV infection at accession among younger recently deployed military personnel born after 1965 was 0.98/1000 (95% confidence interval 0.45‐1.85) and 0.43/1000 (95% confidence interval 0.12‐1.11), respectively. Among these, service‐related incidence was low; 64% of infections were present at the time of accession. With no screening, the cost to the Department of Defense of treating the estimated 93 cases of chronic HCV cases from a single year's accession cohort was 9.3 million. Screening with the HCV antibody test followed by the nucleic acid test for confirmation yielded a net annual savings and a 3.1 million dollar advantage over not screening. Conclusions : Applicant screening will reduce chronic HCV infection in the force, result in a small system costs savings, and decrease the threat of transfusion‐transmitted HCV infection in the battlefield blood supply and may lead to earlier diagnosis and linkage to care; initiation of an applicant screening program will require ongoing evaluation that considers changes in the treatment cost and practice landscape, screening options, and the epidemiology of HCV in the applicant/accession and overall force populations. (Hepatology 2016;63:398–407)